An all-in-one nucleic acid enrichment and isothermal amplification platform for rapid detection of Listeria monocytogenes. (September 2022) - Li, Yong; Yan, Chunyu; Chen, Jiao; Lian, Yunyun; Xie, Yingqiu; Amin, Amr; Wan, Qianyi; Shi, Chao; Ma, Cuiping
Abstract: Listeria monocytogenes is an infectious foodborne pathogen that greatly threatens the public health worldwide. A simple and sensitive detection of L. monocytogenes is extremely important in food safety industry. In this study, we developed an all-in-one platform, which consists of nucleic acid extraction, amplification and visual detection in a single tube. Following a simple bacterial lysis, the released DNA and RNA were highly enriched by a chitosan modified silica membrane (CMSM). Enriched nucleic acids were then directly used for isothermal strand exchange amplification (SEA) and colorimetric detection. The analytical feasibility of this platform was successfully determined by identifying L. monocytogenes with a specific set of primers, and experiments confirmed a detection limit of 1.0 × 10 2  CFU/mL in pure culture, while the limit of detection in L. monocytogenes spiked pork was 1.0 × 10 3  CFU/g without bacterial enrichment and 1.0 × 10° CFU/g following 4 h enrichment. The whole SEA assay takes an hour to complete, allows one-step DNA and RNA amplification and substantially improves the assay sensitivity. In addition, the colorimetric-based visual result readout developed in this study fully alleviates the use of sophisticated equipment. Therefore, the proposed method has great potential for rapid and on-site identification of L. monocytogenes in resource-restricted settings. Highlights: The proposed all-in-one colorimetric SEA method can detect foodborne pathogen in a single tube. DNA and RNA can be enriched simultaneously by chitosan-modified silica membrane for subsequent amplification. Isothermal strand exchange amplification (SEA) realized one-step amplification of DNA and RNA. The results were read out with the naked eye.